2015
DOI: 10.1097/md.0000000000001683
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophilin A in Ruptured Intracranial Aneurysm

Abstract: Cyclophilin A (CyPA), an oxidative stress-induced factor, was found to play an important role in the aneurysm formation. Our working hypothesis was that the plasma level of CyPA in ruptured intracranial aneurysm could predict the neurological outcome.From 2011 to 2013, a total of 36 patients with ruptured saccular intracranial aneurysm were recruited in our study. Before coil embolization, we draw blood samples at the orifice of a culprit aneurysm and in the remote peripheral vein for measurements of the CyPA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 30 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…Quan et al reported that the expression of F2-isoprostanes and F4-neuroprostanes in the plasma of patients with IAs is significantly upregulated compared with healthy subjects, and these may be considered potential biomarkers for IA development (26). Kao et al identified that patients with high levels of aneurysmal cyclophilin A (CyPA) in plasma were 15.66 times more likely to have worse neurological outcomes than those with low levels; this may be a significant prognostic biomarker for poor neurological outcome in IA (27). Compared with serum or tissue samples, blood samples are readily available.…”
Section: Discussionmentioning
confidence: 99%
“…Quan et al reported that the expression of F2-isoprostanes and F4-neuroprostanes in the plasma of patients with IAs is significantly upregulated compared with healthy subjects, and these may be considered potential biomarkers for IA development (26). Kao et al identified that patients with high levels of aneurysmal cyclophilin A (CyPA) in plasma were 15.66 times more likely to have worse neurological outcomes than those with low levels; this may be a significant prognostic biomarker for poor neurological outcome in IA (27). Compared with serum or tissue samples, blood samples are readily available.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously reported that the plasma levels of CyPA are significantly higher in patients with CAD with type 2 DM [13]. Indeed, several studies have demonstrated the role of CyPA as a biomarker of CADs [14][15][16][17][18]. Huang et al [14] reported that the plasma levels of CyPA 1 month after AMI predict the prognosis of the patients.…”
Section: Introductionmentioning
confidence: 98%
“…CyPA is secreted by activated macrophages, lymphocytes, and platelets and mediates the harmful effects of pericytes on BBB disruption ( Seizer et al, 2010 , 2015 , 2016 ; Pan et al, 2020 ). Previous studies have shown that the plasma CyPA level is a new biomarker for the diagnosis of coronary artery disease (CAD) and renal disease progression and is used as a prognostic factor in patients with ruptured intracranial aneurysms ( Satoh et al, 2013 ; Ramachandran et al, 2014 ; Kao et al, 2015 ; El-Ebidi et al, 2020 ; Rath et al, 2020 ). MMP9 is involved in the increase of BBB permeability during AD, which accelerates its onset ( Barr et al, 2010 ; Shackleton et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%